Wood anatomy and dendrochronological potentiality of some woody shrubs from the southern Mediterranean coast in Egypt - Farahat, Emad A.; Gärtner, Holger (Frontiers in Plant Science, 2023)
In tropical and subtropical regions, much research is still required to explore the dendrochronological potential of their trees. This study aims to evaluate the anatomical structure and dendrochronological potential of three Mediterranean desert shrubs in Egypt (Lycium schweinfurthii var. schweinfurthii, L. europaeum, and Calligonum polygonoides subsp. comosum) supported by X-ray density. The results showed that the target species had distinct growth rings at macroscopic and microscopic levels. The vessel traits reflected the adaptability of each species with the prevailing arid climate conditions. After the exclusion of the non-correlated series, we obtained three site chronologies that cover the years 2013-2022 for L. schweinfurthii, 2012-2022 for L. europaeum, and 2011-2022 for C. comosum. The mean series intercorrelation was 0.746, 0.564, and 0.683 for L. schweinfurthii, L. europaeum, and C. comosum, respectively. The EPS values ranged from 0.72 to 0.80, while the SNR ranged from 9.1 to 21.5. Compiling all series of L. schweinfurthii raised the EPS value to 0.86. The chronologies developed for the studied species were relatively short since we dealt with multi-stemmed shrubs. The average percentage difference between latewood density (LWD) and earlywood density (EWD) in C. comosum, L. europaeum, and L. schweinfurthii¬ were 11.8% ± 5.5, 5.2%± 1.87, and 3.6% ±1.86, respectively. X-ray densitometry helped in the precise determination of the ring borders of the studied species. Generally, the radial growth of the target species had a positive correlation with temperature and precipitation during the wet season (winter), while negatively correlated with temperature for the rest of the year, particularly in summer. We assume that ring formation starts at the beginning of the long vegetative stage, then the rest of the assimilated carbohydrates are directed to the flowering and fruiting at the end of the vegetative stages. For more efficient dendrochronological studies on subtropical and Mediterranean trees, we recommend carrying out xylogenesis studies, collection of phenological data, sampling of 45-80 trees per species, using new techniques, and choosing homogeneous and close sites for wood sampling.